Redo Aortic Valve Replacement After Prior Transcatheter versus Surgical Aortic Valve Replacement: Insights from Western Experience - Arber Aliu; Klodiana Durici; Ira Lazo; Altin Veshti (Albanian Journal of Trauma and Emergency Surgery)
Introduction: The demand for reoperation on the aortic valve in Albania is rising, mirroring the increasing average age of the population and the subsequent rise in patients requiring aortic valve surgery. This trend underscores the need for this informative article, which aims to provide insights into the risks and outcomes of aortic valve reoperations, particularly in light of efforts by interventional cardiologists to expand the indications for TAVR to younger and lower-risk patients. Data from the Society of Thoracic Surgeons (STS) National Database reveal results that warrant attention, with concerns over reoperations after TAVR growing, mainly due to the uncertain feasibility of repeat TAVR.